Comparison of success between external and endonasal dacryocystorhinostomy in primary acquired nasolacrimal duct obstruction in South India population - Flarence MR; Meduri Nikhitha Kishore; Muderla Rajesh (Asian Journal of Medical Sciences, 2024)
Background: Dacryocystorhinostomy (DCR) has been the standard procedure for primary acquired nasolacrimal duct obstruction (PANDO) for many years. This process can be performed either using an endoscopic or external approach. Aims and Objectives: The aim is to evaluate the results and recurrence rates of external DCR (ExDCR) and endonasal DCR (EDCR) surgery in patients with PANDO in the South Indian population. Materials and Methods: Medical records were reviewed in all patients who underwent surgery for PANDO between December 2021 and August 2023 at Government Medical College Mahabubabad. Results: This study was conducted in 92 patients; 34 males (36.96%) and 58 females (63.04%) were the gender split. ExDCR was used in 52 (56.52%) of the cases, and EDCR was used in 40 (43.487%) of the cases. Operation success rates of these data revealed that 50 (54.34%) cases were recorded as successful, 24 (26.10%) of the cases were accepted as partially successful, and 18 (19.56%) of the cases were deemed unsuccessful. There was no statistically significant difference between success rates and recurrences in both groups (P>0.05). Conclusion: Endoscopic DCR produced simple, minimally invasive, and preferable results compared to ExDCR in the South Indian population. Although the success of ExDCR is higher and the recurrence is lower than endoscopic DCR, with the outcomes of this study, endoscopic DCR can be tried as the first choice to protect the patient from major surgery and anesthesia in PANDO.